THE CORRELATION BETWEEN METACOGNITIVE READING STRATEGIES AND READING COMPREHENSION OF ENGLISH DEPARTMENT STUDENTS - Kezia Zhanetta Alfangca; M.N. Siti Mina Tamah (Widya Mandala Surabaya Catholic University, 2017)
The objectives are to find the type and frequency Global, Problem Solving, and Support reading strategies the students use during reading, to find the correlations between each three reading strategies and reading comprehension. The instruments used are a survey on metacognitive reading strategies adapted from MARSI and SILL and a reading comprehension test. The findings revealed that PROB strategies were used the most, followed by GLOB strategies, and SUPP strategies. The correlations showed that (1) a positive, moderate (at .66) correlation between GLOB and reading comprehension, (2) a positive, strong correlation (at .72) between PROB and reading comprehension, and (3) a positive, weak correlation (at .26) between SUPP and reading comprehension.